Quantitative Analysis of Postural Balance in Faller and Nonfaller Patients with Parkinson’s Disease - Do Young Kwon; Yuri Kwon; Ji-An Choi; Junghyuk Ko; Ji-Won Kim (Parkinson's Disease)
Background. Postural instability has been identified as a fall risk factor with a significant impact on the quality of life of patients with Parkinson’s disease (PD). The aim of this study was to compare the center of pressure (COP) between faller and nonfaller patients with PD during static standing. Methods. Thirty-two faller patients and 32 nonfaller patients with PD participated in this study. All patients performed the static balance test on a force plate. COP data were recorded during quiet standing. Mean distance, sway area, mean velocity, mean frequency, and peak power were derived from the COP data. Statistical analysis was performed using independent t-tests to compare faller and nonfaller patients. Results. Fallers presented a greater average distance, wider sway area, faster average speed, and greater peak power than nonfallers (p < 0.05). In contrast, no significant group differences were observed in peak frequency and mean frequency (p > 0.05). Conclusions. Although falls occur during dynamic activities, our study demonstrated that even a safe and simple static postural balance test could significantly differentiate between faller and nonfaller patients. Thus, these results suggest that quantitatively assessed static postural sway variables would be useful for distinguishing prospective fallers among PD patients.